A perinuclear α-helix with amphipathic features in Brl1 promotes NPC assembly - Vitale, Jlenia; Kahn, Azqa; Neuner, Annett; Schiebel, Elmar (Molecular biology of the cell, 2022)
How nuclear pore complexes (NPCs) assemble in the intact nuclear envelope (NE) is only rudimentarily understood. Nucleoporins (Nups) accumulate at the inner nuclear membrane (INM) and deform this membrane toward the outer nuclear membrane (ONM), and eventually INM and ONM fuse by an unclear mechanism. In budding yeast, the integral membrane protein Brl1 that transiently associates with NPC assembly intermediates is involved in INM/ONM fusion during NPC assembly but leaving the molecular mechanism open. AlphaFold predictions indicate that Brl1-like proteins carry as common motifs an α-helix with amphipathic features (AαH) and a disulfide-stabilized, anti-parallel helix bundle (DAH) in the perinuclear space. Mutants with defective AαH (brl1F391E, brl1F391P, brl1L402E) impair the essential function of BRL1. Overexpression of brl1F391E promotes the formation of INM and ONM enclosed petal-like structures that carry Nups at their base, suggesting that they are derived from an NPC assembly attempt with failed INM/ONM fusion. Accordingly, brl1F391E expression triggers mislocalization of Nup159 and Nup42 and to a lesser extent Nsp1, which localize on the cytoplasmic face of the NPC. The DAH also contributes to the function of Brl1, and AαH has functions independent of DAH. We propose that AαH and DAH in Brl1 promote INM/ONM fusion during NPC assembly.